Delivery of cations (Mg2+, Al3+, Ga3+, Sn2+, Cr3+, Fe3+) into the cells by anthocyanins through Physico-chemical assessment: A molecular simulation study - Mollaamin, Fatemeh; Monajjemi, Majid (Sin-Chn Scientific Press Pte. Ltd (Singapore) (Publications), 2024)
Anthocyanins (ACNs) are secondary metabolites responsible for most of the red to purple pigmentation found in flowers, fruits, and leaves. Clusters of metal ions of Mg2+, Al3+, Ga3+, Sn2+, Cr3+, Fe3+ joined to ACNs in water media were studied for unraveling the color shifting of different complexes of these structures in the low ranges of pH. In this verdict, it has been studied the metallic cations diffusing of deprotonating for the anthocyanin (ACN) (B)-ring of Malvidin (Mal), Peonidin (Peo), Delphinidin (Del), Pet, and Cyanidin (Cya) in water. The difference of heat of formation (∆Hf) among clusters of metallic cations jointed to ACNs has been illustrated toward the double bonds and carbonyl groups by the chelation of (B)-ring for cyanidin, delphinidin and petunidin ACNs in two media of gas and water that explains the stability and color of [ACN-metallic cations] cluster chelation. The complexes of Ga3+ → Pet, Cr3+ → Pet, Mg2+ → Pet and Al3+ → Cya, Ga3+ → Cya, Mg2+ → Cya have indicated the maximum absorbance in the low concentration. The mechanism of cation-induced ACNs mainly depends on the location of active zones of functionalized O-atoms in ACN and divalent or trivalent cations characteristics. Regarding the obtained results, regular consumption of some vegetables and fruits, which are rich in ACN molecules, should be helpful to stop viral infectious by decreasing pathogenicity and propagation of viral diseases.